2021
DOI: 10.1007/s00248-021-01867-9
|View full text |Cite|
|
Sign up to set email alerts
|

Instability and Stasis Among the Microbiome of Seagrass Leaves, Roots and Rhizomes, and Nearby Sediments Within a Natural pH Gradient

Abstract: Seagrass meadows are hotspots of biodiversity with considerable economic and ecological value. The health of seagrass ecosystems is influenced in part by the makeup and stability of their microbiome, but microbiome composition can be sensitive to environmental change such as nutrient availability, elevated temperatures, and reduced pH. The objective of the present study was to characterize the bacterial community of the leaves, bulk samples of roots and rhizomes, and proximal sediment of the seagrass species C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Microbial diversity is influenced by various factors, such as sediment depth, water pH, and seagrass species (Banister et al, 2022). We found that the upper sediment layers had a higher alpha diversity of bacteria and archaea, whereas microbial eukaryotes were more abundant in the lower layers.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial diversity is influenced by various factors, such as sediment depth, water pH, and seagrass species (Banister et al, 2022). We found that the upper sediment layers had a higher alpha diversity of bacteria and archaea, whereas microbial eukaryotes were more abundant in the lower layers.…”
Section: Discussionmentioning
confidence: 99%
“…roots, rhizomes, and leaves), as well as between species, which have a vast geographical distribution and are subject to a variety of environmental conditions. There are also differences between seagrass microbiomes and those of the adjacent seawater and surrounding sediment [44][45][46][47].…”
Section: Seagrass Biology Evolution and Biodiversitymentioning
confidence: 99%
“…It lives in open waters on sandy and muddy substrates, but it can also colonize coastal lagoons, tolerating natural salinity fluctuations [ 29 , 30 , 31 , 32 ]. Little is known about C. nodosa ’s epiphytic bacterial communities [ 25 , 33 , 34 ]. These studies showed that C. nodosa harbours a rich microbial community even under different pH changes [ 33 ] and maintains its host-specific microbial community when in syntopy with the invasive seaweed Caulerpa cylindracea [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about C. nodosa ’s epiphytic bacterial communities [ 25 , 33 , 34 ]. These studies showed that C. nodosa harbours a rich microbial community even under different pH changes [ 33 ] and maintains its host-specific microbial community when in syntopy with the invasive seaweed Caulerpa cylindracea [ 34 ].…”
Section: Introductionmentioning
confidence: 99%